EDUKASI BIJAK MENGGUNAKAN ANTIBIOTIK DI KECAMATAN RAPPOCINI, KELURAHAN BUAKANA - ramadani, ananda; A. Tenriugi Daeng Pine; Imansyah, Maulana Zulkarnain; Muhammad Tahir; Raymond Arief N. Noena; Taufiq; Syam, Rika Amalia; Yulya Irmawati (Akademi Farmasi Yamasi Makassar, 2024)
Antibiotic resistance is a growing public health problem globally, largely due to the misuse and overuse of antibiotics. This community service project aimed to educate the residents of Rappocini District, specifically in Buakana Village, on the wise use of antibiotics. Through workshops and discussions, we provided participants with information on the dangers of antibiotic misuse, the importance of following prescribed dosages, and the consequences of self-medicating without professional guidance. The program aimed to enhance public awareness and encourage rational antibiotic use to prevent resistance. Feedback from participants indicated improved understanding and commitment to using antibiotics responsibly. This community service is expected to contribute to better public health outcomes by promoting prudent antibiotic use.